Hyperbole and Personification Used by Food Reviewers on TikTok Application as Promotion Strategy - Fikry Prastya, Syahputra (Journal Business Administration: Entrepreneurship and Creative Industry, 2023)
The increasingly advanced digital world also has an impact on shifting the way the world community trades. One of them is promotional media which is increasingly being carried out on social media such as Facebook, Instagram and TikTok. This research examines various language styles in food reviewers in promoting Eat Sambel. This research data focuses on comparative language styles (personification) and contradiction language styles (hyperbole). The purpose of this research is to describe and explain the style of language used and its meaning by food reviewers in promoting Eat Sambel products. The research method used in this study is qualitative descriptive. Data collection techniques use documentation techniques. Based on the results of data analysis found in several food reviewer videos on the TikTok application, the figure of contradiction (hyperbole) was more dominant than the figure of comparative (personification). In other words, these food reviewers prefer to highlight the products they are reviewing rather than comparing them with other products which will later lead to debating.